Concurso de ensayos: Tendiendo puentes 2016 francisco, política y solidaridad - Rubio Morales, Ricardo A. (2016)
Apostolic Journey of the Holy Father Francisco to Ecuador, Bolivia and Paraguay (2, 2015, Santa Cruz de la Sierra, Bolivia). Participation in the Second World Meeting of Popular Movements. Santa Cruz de la Sierra, Bolivia, Libreria Editrice Vaticana, 2015. pp. 2-11